Childhood Physical Neglect Is Associated With Exaggerated Systemic and Intracellular Inflammatory Responses to Repeated Psychosocial Stress in Adulthood - Schreier, Hannah M. C.; Kuras, Yuliya I.; McInnis, Christine M.; Thoma, Myriam V.; St Pierre, Danielle G.; Hanlin, Luke; Chen, Xuejie; Wang, Diana; Goldblatt, Dena; Rohleder, Nicolas (Frontiers in Psychiatry, 2020)
Experiences of child maltreatment are associated with a host of adverse mental and physical health outcomes in adulthood. Altered reactivity to psychosocial stress exposure may partially explain known associations between early experiences of maltreatment and later life health. The present study focuses on examining whether experiences of child maltreatment are associated with physiological reactions to initial and repeated psychosocial stress in adulthood. To this end, 44 healthy adults (52% male, aged 18-65) completed the Childhood Trauma Questionnaire to provide information about exposure to child maltreatment and completed the Trier Social Stress Test (TSST) on two consecutive days. Peripheral blood was collected prior to as well as 30 and 120 minutes following the TSST on each day. Plasma Interleukin-6 (IL-6) and gene expression of IL-6, IL-1β, nuclear factor-kB (NF- kB), and inhibitor of kB (IkB) were measured from each blood sample. Total CTQ scores were unrelated to plasma IL-6 and gene expression (ps > .10) but a history of childhood physical neglect was associated with increased interleukin-1β (β = .35; p = .02; R 2 = .19) and nuclear factor-kB (β = .30; p = .046; R 2 =.13) expression following initial stress. Following repeated exposure to the TSST, childhood physical neglect was associated with increased plasma IL-6 reactivity (β = .34; p = .02; R 2 =.16) and increased expression of nuclear factor-kB (β = .31; p = .04; R 2 = .08). Finally, childhood physical neglect was associated with decreased habituation following repeated exposure to the TSST. Other CTQ subscales were not related to plasma IL-6 and gene expression when considered individually. Results from this study are suggestive of a unique effect of childhood physical neglect on the physiological stress response following initial and repeated exposure to a common psychosocial stressor. This provides important directions for future research because the effect of childhood physical neglect on long-term neglect are not well understood and in need of further investigation.